Multilingual Constructicon - Språkbanken Text (University of Gothenburg, 2024)
A multilingual Constructicon

Ett flerspråkigt konstruktikon
Flerspråkigt Konstruktikon
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik